2017
DOI: 10.1109/tvt.2017.2651949
|View full text |Cite
|
Sign up to set email alerts
|

Online Power and Time Allocation in MIMO Uplink Transmissions Powered by RF Wireless Energy Transfer

Abstract: Abstract-Wireless energy transfer (WET) has been a promising technology to tackle the lifetime bottlenecks of energy-limited wireless devices in recent years. In this paper, we study a WET enabled multiple input multiple output (MIMO) system including a base station (BS) and a user equipment (UE), which has a finite battery capacity. We consider slotted transmissions, where each slot includes two phases, namely downlink (DL) WET phase and uplink (UL) wireless information transmission (WIT) phase. In the WET ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In [5], a RFpowered massive multiple input multiple output (MIMO) system adopted slotted transmissions, in which each slot was divided into three phases for channel estimation, downlink power transmission, and uplink data transmission, respectively. In [6], an online power and time allocation algorithm was studied for a WET powered MIMO system with its focus on energy receiving sensitivity with a finite battery capacity. Robust resource allocation methods in non-linear EH model based MIMO WPCNs were investigated in [7].…”
Section: A Related Workmentioning
confidence: 99%
“…In [5], a RFpowered massive multiple input multiple output (MIMO) system adopted slotted transmissions, in which each slot was divided into three phases for channel estimation, downlink power transmission, and uplink data transmission, respectively. In [6], an online power and time allocation algorithm was studied for a WET powered MIMO system with its focus on energy receiving sensitivity with a finite battery capacity. Robust resource allocation methods in non-linear EH model based MIMO WPCNs were investigated in [7].…”
Section: A Related Workmentioning
confidence: 99%
“…Here, E(·) and Tr(·) denote statistical expectation and the trace of a matrix, respectively. By ignoring the negligible receiver noise power for energy harvesting, the amount of energy harvested at device k under a linear energy harvesting model 1 [7], [8], [10], [13], [20] can be expressed as…”
Section: A System Modelmentioning
confidence: 99%
“…From (8), it is observed that when DL WPT is activated, the optimal W is rank one and independent of the users' initial energy E I k . This suggests that to maximize WSR, the optimal energy beamforming direction does not depend on the initial energy levels of the devices, E I k .…”
Section: B Optimal Resource Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Multiple Access: While single-device scenarios have been considered in [16], [19], [22], [23], [25], WPCNs may also be used for multiple WDs [2], [13], [14], [17], [18]. When multiple devices are considered, multiple access techniques should be utilized for the UL channels.…”
Section: ) Duplexingmentioning
confidence: 99%